Видатний дослідник народних мелодій - Гайдай, М. (Народна творчість та етнографія, 2005)
This is an unpublished (written at the soviet times by M.P.Hayday) article about the musicological aspect of K. Kvitka's work is presented now by his sun (well knowing Ukrainian folklorist) M.Hayday. This article comes to print at the time when Ukraine celebrates the 125th birthday Anniversary of K. Kvitka and the reader can see the general overview of the Kvitka's work during his life time on collecting and organizing folk songs. The work on the rhythms of folk melodies and other theoretical questions of Kvitka's musicological studies are presented as well.